POST-EXERTION CASCADE: DECODING THE HAEMATO-BIOCHEMICAL INDICES OF DEHYDRATION IN ELITE HORSES - Atata, Jamila Abdulhamid; Osho, Barakat Olaitan; Ajadi, Abdullateef Abiodun; Adam, Mohammed; Jegede, Henry Olanrewaju (FUDMA JOURNAL OF SCIENCES, 2025)
Dehydration is a significant concern in elite racing horses, potentially triggering substantial haemato-biochemical that can compromise their physiological well-being and athletic performance. This study investigated these responses in 15 Arabian horses subjected to a standardized strenuous exercise protocol. Blood samples were collected before and after a 14,000-meter endurance race conducted under hot ambient conditions (average 36.9°C). Analysis of haemato-biochemical parameters, including packed cell volume (PCV), haemoglobin (Hb), erythrocyte count, total and differential leukocyte counts, total protein, albumin, glucose, urea, creatinine, aspartate aminotransferase (AST), creatine kinase (CK), and lactate dehydrogenase (LDH), was performed using established laboratory methods. Post-exercise, significant increases were observed in PCV, Hb, total protein, albumin, urea, and creatinine, indicative of dehydration. Concurrently, elevated AST, CK, and LDH levels suggested muscular damage and metabolic stress. The study's findings underscore the marked alterations in these parameters following intense exercise in Arabian horses. Continuous monitoring of haemato-biochemical parameters is crucial for preventing dehydration and muscle damage in these equine athletes. Implementing targeted strategies for optimal hydration and exercise management is therefore recommended for veterinary practitioners.
Keywords: Arabian Horses; Hydration status; Muscle damage; Physical exertion; Stress